วาสันติกสวัปนะ : การดัดแปลง A Midsummer night s dream ของเชกสเปียร์เป็นละครสันสกฤต - พิชญาวุฒิ กุมภิโร (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This thesis aims at analyzing the adaptation strategies of R. Kṛṣṇamācārya s Vāsantikasvapna and compare them with Shakespeare s A Midsummer Night s Dream, especially Acts I and II. The research method is divided into two parts. The first part is an analytical study of the adaptation of Sanskrit drama by using the Nāṭyaśāstra as the main study. The second part is a comparative study to significant similarities and differences. The results of the study reveal that R. Kṛṣṇamācārya completely converted A Midsummer Night s Dream into a Sanskrit drama based on Nāṭyaśāstra, namely: It is Prakaraṇa, consisting of 5 acts, complete with elements of Sanskrit drama such as the Nāndī, Prastāvanā, Praveśaka, Viṣkambhaka and Bharatavākya. The characters use language according to their status. The prosody that appears consists of verse and prose that reveals the sensitivity and power of Sanskrit in harmony with the Alaṃkāra, Bhāva, Rasa, Kāvyaguṇa and Vṛtti. In the comparative study of the two plays, there are two main methods of adaptation to Sanskrit plays, namely the literal in other places and the rendering is free in some places. The second method is divided into three methods: enlargement, deviations in details, and omission. All of these methods correspond to adaptations of Peter Newmark s translation theory and some proposed set of strategies for translating the proper name allusions of Ritva Leppihalme. Vāsantikasvapna is therefore highly prized in both the Sanskrit and adaptation version of the play.